2021
DOI: 10.37859/jae.v11i1.2490
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Retaliasi, Emosi Negatif, Dan Komitmen Organisasi Terhadap Kecenderungan Melakukan Whistleblowing

Abstract: Financial crime is increasingly rampant these days. The fact is financial crimes are often seen directly by internal parties in an organization. It is very important to analyze the intention of an employee to do whistleblowing. The purpose of this study was to examine the effect of retaliation, negative emotions (guilt and shame), and organizational commitment on an individual's intention to whistleblowing. This research was conducted in all branches of PT. Telkomsel in Riau Province. The sampling method used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…H6: Peer-reporting type moderates the influence of perceived personal cost on internal whistleblowing intentions. Hannah et al (2011) argue that in ethical decisions setting, contextual variables are the most crucial factor before blowing the whistle and inconsistencies from prior study regarding variables such as microsocial ethical environment (Lee & Fargher, 2013;Dalton & Radtke, 2013;Ahyaruddin & Asnawi, 2017;Taripudin & Umar, 2020), anonymous reporting channel (Kaplan & Schultz, 2007;Ayers & Kaplan, 2005;Kaplan et al, 2009;Jenkel & Haen, 2012;Gao et al, 2015;Park et al, 2014) and perceived personal cost (Callahan & Collins, 1992;Park et al, 2005;Cho & Song 2015;Kennett et al, 2010;Keenan, 2002;Winardi, 2013) encourage this study to re-examine and add a moderating variable that is peer-reporting type. The direct effect from three exogenous variables is theoretically constructed from rational choice theory, meanwhile the moderating variable is built on grid-group cultural theory perspective.…”
Section: Moderating Effect Of Peer-reporting Type On the Influence Of...mentioning
confidence: 97%
See 1 more Smart Citation
“…H6: Peer-reporting type moderates the influence of perceived personal cost on internal whistleblowing intentions. Hannah et al (2011) argue that in ethical decisions setting, contextual variables are the most crucial factor before blowing the whistle and inconsistencies from prior study regarding variables such as microsocial ethical environment (Lee & Fargher, 2013;Dalton & Radtke, 2013;Ahyaruddin & Asnawi, 2017;Taripudin & Umar, 2020), anonymous reporting channel (Kaplan & Schultz, 2007;Ayers & Kaplan, 2005;Kaplan et al, 2009;Jenkel & Haen, 2012;Gao et al, 2015;Park et al, 2014) and perceived personal cost (Callahan & Collins, 1992;Park et al, 2005;Cho & Song 2015;Kennett et al, 2010;Keenan, 2002;Winardi, 2013) encourage this study to re-examine and add a moderating variable that is peer-reporting type. The direct effect from three exogenous variables is theoretically constructed from rational choice theory, meanwhile the moderating variable is built on grid-group cultural theory perspective.…”
Section: Moderating Effect Of Peer-reporting Type On the Influence Of...mentioning
confidence: 97%
“…Several previous studies have found that these three variables significantly affect whistleblowing. Several studies contradict theories, such as research conducted by (Ahyaruddin & Asnawi ,2017), which states that the ethical environment has no significant effect on whistleblowing. (Jenkel & Haen, 2012) and (Kaplan et al, 2009) provide empirical evidence that anonymous reporting channel have no significant effect on whistleblowing.…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies related to professional commitment and moral reasoning were carried out by Asni et al (2018); Dwirandra and Suryanawa (2018); Hermawan and Sari (2018); Ismail and Yuhanis (2018); Jasmine and Susilawati (2019); Husnah (2020); and Pangestu and Rahajeng (2020) show that professional commitment and moral reasoning have a positive influence on ethical decisions and ethical behavior. Research conducted by Faisal (2007); Januarti (2011); Ahyaruddin and Asnawi (2017); and Wirakusuma (2019) found different results that professional commitment and moral reasoning did not affect ethical perceptions and decisions.…”
Section: Introductionmentioning
confidence: 95%
“…Whistleblowing dianggap sebagai alat berharga dalam strategi tata kelola perusahaan yang mengungkap laporan pelanggaran, yang demikian membantu menjaga keamanan dan melindungi reputasi perusahaan (Ahyaruddin & Asnawi, 2017). Whistleblowing relevan dan berperan penting dalam penerapan tata kelola perusahaan yang merupakan bahan utama pertumbuhan organisasi.…”
Section: Whistleblowing Sebagai Strategi Tata Kelola Perusahaanunclassified
“…Survei yang dilakukan oleh (Association of Certified Fraud Examiners, 2019) menyebut laporan pengungkapan fraud tertinggi yaitu sebesar 22,6% disumbang oleh metode hotline/whistle blower system diikuti dengan kebijakan antri-fraud pada organisasi sebesar 13,8%. Menurut (Ahyaruddin & Asnawi, 2017) terungkapnya kasus fraud sebagian besar disumbang oleh laporan whistleblower, sedangkan sisanya terungkap dari internal audit, internal control, ataupun terungkap dengan tidak sengaja. Sebagaimana dijelaskan dalam laporan (Association of Certified Fraud Examiners, 2019) empat media pengungkapan fraud terbanyak berasal dari laporan 38,9%, audit internal 23,4%, lainnya 15,1%, dan 9,6% audit eksternal.…”
unclassified